Numerical simulations of NBI fast ion loss with RMPs on the EAST tokamak. (14th July 2020) - Xu, Yingfeng; Li, Li; Hu, Youjun; Liu, Yueqiang; Guo, Wenfeng; Ye, Lei; Xiao, Xiaotao
Abstract: Fast ion losses in the presence of resonant magnetic perturbations (RMPs) on the EAST tokamak have been simulated by using the Monte Carlo orbit-following code GYCAVA (Xu et al 2019 Comput. Phys. Comm. 244 40). Fast ions produced by the co-current tangential neutral beam injection (NBI) were considered. The initial distribution of NBI fast ions was numerically computed by the TGCO code and the n = 1 vacuum and response RMP fields were numerically computed by the MHD code MARS-F (Liu et al 2000 Phys. Plasmas 7 3681). It is found that fast ion losses increase almost linearly with the RMP coil current. Poincaré plots show that fast ion losses in the presence of RMPs on EAST are mainly due to the orbit stochasticity induced by RMPs. The collision effect, including the slowing down and the pitch angle scattering, on fast ion losses have also been numerically studied. The synergy effect of RMPs and collision-induced pitch angle scattering can enhance the particle loss of fast ions. The collision effect, including the effective ion charge number effect, on the power loss of fast ions is weak. Fast ion losses increase with the effective ion charge number increasing, which is related to the pitch angle scattering effect. The plasma response to RMPs can enhance or reduce fast ion losses. The plasma response effect on fast ion losses depends on the RMP coil phasing, that is, the phase difference between the upper and lower coils. The heat loads on the outer wall clearly follow the n = 1 periodicity of the RMP coil configuration. Positions of maximum heat loads are closely related to the coil phasing of RMPs. These mean that the magnetic topology of RMPs is responsible for the toroidal distribution of heat loads.